2017
DOI: 10.22159/ijpps.2017v9i10.21455
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antihyperlipidaemic Activity of Nelumbo Nucifera Gaertn Ethanol Seed Extract in Streptozotocin Induced Diabetic Rats

Abstract: Objective: The main objective of the study was to investigate the effect of ethanol seed extracts of Nelumbo nucifera Gaertn (Nymphaeaceae) as antihyperglycemic, anti-hyperlipidemic and antioxidant activity in streptozotocin-induced diabetic rats.Methods: Diabetes was induced in wistar albino rats by administration of streptozotocin (single intraperitoneal dose of 60 mg/kg B. W). The ethanol extract of N. nucifera seed at a dose of 200 and 400 mg/kg body weight was administrated at a single dose per day to STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The pathogenesis of diabetes mellitus including the chances of managing the oral administration of hypoglycemic herbal treatment have been extensively studied. Our results of antidiabetic effect of N. Nucifera agree with 8 who proved the reduction effect of alcoholic extract of N. Nucifera on blood glucose level in induced diabetic rats. It was found that the level of A1CHb levels in the rats was reduced to a significant amount.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pathogenesis of diabetes mellitus including the chances of managing the oral administration of hypoglycemic herbal treatment have been extensively studied. Our results of antidiabetic effect of N. Nucifera agree with 8 who proved the reduction effect of alcoholic extract of N. Nucifera on blood glucose level in induced diabetic rats. It was found that the level of A1CHb levels in the rats was reduced to a significant amount.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies proved the hypolipidemic, antihypertensive and hypoglycemic effects of H. Thebacia and N. Nucifera 14,5,12,7,18,19,8 , and 1 . Our results showed that H. Thebacia and N. Nucifera have significant lowering effect to lipid profile that comprises of the complete levels of cholesterol, as well as Triglycerides including low density lipoprotein.…”
Section: Discussionmentioning
confidence: 88%
“…This results in fragmentation of DNA by means of production of ROS. STZ causes massive destruction of β-cells of the islets of Langerhans resulting in the insulin synthesis and secretion [16]. The toxic effect of STZ is not restricted to abolishment of pancreatic β-cells but also causes oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…5 Seeds are used in folk medicines as treatment of tissue inflammation, cancer, skin disease, and leprosy. 6…”
Section: Introductionmentioning
confidence: 99%